Implementasi Sistem Penjaminan Mutu Internal (SPMI) pada Masa Pandemi Covid-19 di Sekolah Menengah Pertama - Hamidatul Ula; M. Yunus Abu Bakar (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
The Internal Quality Assurance System (SPMI) is a quality assurance system implemented in schools to achieve and exceed the National Education Standards (SNP). The Covid-19 Pandemic requires the government to issue new policies, especially policies related to education. These new policies certainly have an impact on the implementation of SPMI in schools. This study aims to determine the implementation of the quality assurance system at SMP Islam Brawijaya during the Covid-19 Pandemic. This is a case study that uses a qualitative descriptive method. Data was collected through observation, interviews, and document studies. The results of the study indicate that the implementation of SPMI in SMP Islam Brawijaya begins with the School Self Evaluation (EDS) process which includes eight standards in the SNP by the School Education Quality Assurance Team (TPMPS); preparation of quality fulfillment plans which are then contained in the Work Plan and Requirements (RKS) and School Activity Plans and Budgets (RKAS); implementation of quality fulfillment, monitoring, and evaluation by TPMPS. However, the Covid-19 Pandemic situation has caused problems experienced by TPMPS in carrying out their duties, so that the implementation of SPMI has not run optimally. The entire series is documented in the form of a quality report card, and it is proven that the results of the quality report card have decreased.